Development Of Cisplatin Delivery Nanosystem With Chitosan-coated Titania Nanotube Arrays Platform Targeting For Nasopharyngeal Carcinoma - Effendy, Wan Nuramiera Faznie Wan Eddis (2022)
Present chemodrug treatment for advanced-stage nasopharyngeal carcinoma (NPC) via cisplatin (CDDP) have limitations such as non-specific biodistribution, dose-limiting toxicities, the emergence of resistant cancer cells and various side effects. Targeted and controlled release of CDDP delivery using titania nanotube arrays (TNA) smart nanosystem may offer a new approach to improve those limitations. TNA was fabricated, characterised, and optimised by electrochemical anodisation for CDDP loading in this study. The CDDP-loaded TNA (CDDP-TNA) encapsulation efficiency was studied using two methods: top-filling and immersion methods. The characterisation was performed using field emission scanning electron microscopy, energy dispersive X-ray, X-ray diffraction, ion-coupled plasma–optical emission spectrometry, Fourier transform infrared spectroscopy, spectrophotometry and wettability test. Biopolymer chitosan-coated CDDP- TNAs were optimised in terms of concentrations of acetic acid for 10 mg/mL chitosan preparation, coating methods, number of coating layers, and biocompatibility of chitosan coating layers. The CDDP release activities from chitosan-coated CDDP-TNA were further investigated in various phosphate buffer saline immersion systems with different pH values, simulated body fluid, and targeted NPC in vitro system. Further intracellular observation was performed using fluorescence microscopy.